2023
DOI: 10.1037/rel0000440
|View full text |Cite
|
Sign up to set email alerts
|

Faith development as change in religious types: Results from three-wave longitudinal data with faith development interviews.

Abstract: Faith, as a way of how people understand God and the world and make or discover meaning in their life, is characterized by individual differences and changes over the lifetime. Our research investigates these changes over the lifespan in terms of hierarchically ordered types that are the elements in our developmental model, which is a critical advancement and modification of Fowler's theory of faith development. This study is the first to investigate whether there is development in faith over the adult lifespa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Consistent with cross-sectional research, these studies found that baseline levels of agreeableness, conscientiousness, and/or openness predicted individual differences in changes in religiosity when controlling for prior levels of religiosity. Specifically, higher levels of these traits in adolescence or early adulthood relative to other people predicted greater relative increases in religiosity over time (Gebauer et al, 2014; McCullough et al, 2005; Streib et al, 2021). Although these studies indicated that personality traits predict changes in religiosity, design restrictions limited their conclusions about change in religiosity and precluded an examination of reciprocal effects between personality and religiosity.…”
Section: Cross-sectional Links Between Personality and Religiositymentioning
confidence: 99%
“…Consistent with cross-sectional research, these studies found that baseline levels of agreeableness, conscientiousness, and/or openness predicted individual differences in changes in religiosity when controlling for prior levels of religiosity. Specifically, higher levels of these traits in adolescence or early adulthood relative to other people predicted greater relative increases in religiosity over time (Gebauer et al, 2014; McCullough et al, 2005; Streib et al, 2021). Although these studies indicated that personality traits predict changes in religiosity, design restrictions limited their conclusions about change in religiosity and precluded an examination of reciprocal effects between personality and religiosity.…”
Section: Cross-sectional Links Between Personality and Religiositymentioning
confidence: 99%